Isothermal adsorption modelling of Pupuru flour - ADESHINA FADEYIBI (Croatian Journal of Food Science and Technology, 2020)
The amount of moisture adsorbed by stored food products usually varies with temperature and relative humidity at a constant pressure. This research was carried out to determine the sorption isotherm behaviour of pupuru flour in the temperature and water activity (aw) ranges of 10−50 oC and 0.10−0.93 using gravimetric method. The Guggenheim-Anderson-De Boer (GAB), Brunauer-Emmett-Teller (BET), Oswin and Smith sorption equations, formulated for the sorption characterization of starchy foods, were used to constitute the models. The results show that the sorption isotherm curve is similar to a Type II classification typical of starchy foods. Also, the sorption parameters (Mo, C and K) were generally higher for the products stored at 10 oC and 0.10 aw. The parameter K decreases with an increase in the temperature for the GAB and the Smith models, but remains inconsistent for the Oswin model. The Mo increases with an increase in the temperature for the GAB and Smith models. The GAB, Oswin and Smith models were generally adequate and valid with an MSE< 10% and a high degree of fitness (R2 and R2adj > 90%). This indicates their ability to predict the sorption isortherm characteristics of the pupuru flour within its range of the aw and the storage temperature.